Mapping content management system features with knowledge sharing elements for creating online knowledge sharing model - Salamat, Mohamad Aizi; Md. Fudzee, Mohd Farhan; Mahdin, Hairulnizam; Mohamad, Kamaruddin Malik (2006)
The emerging of knowledge management promises a great impact towards organization’s productivity.The main idea is to enable knowledge sharing between knowledgeable staff while bringing the tacit knowledge into surface.However, the most challenging part in creating any portal is to design and develop the portal from sketch.Moreover, it acquires high expertise and cost; thus making it far from success.The arising of Content Management System (CMS) especially Open Source Software (OSS) provides alternative solution to cater with the mentioned drawbacks.The purpose of this paper is to propose a knowledge sharing model using CMS. The key activity in this research is to map the CMS features with knowledge sharing elements, by reviewing particular models.Significantly, the adoption of the proposed model in developing knowledge portal will decrease the design and development time, while using OSS can reduce the cost.